Experimental investigation on interface shear strength of composite PVC encased macro-synthetic fibre reinforced concrete walls. (December 2021) - Far, Harry; Nejadi, Shami
Abstract: Over the past decade, Polyvinyl Chloride (PVC) stay-in-place formwork has become a popular alternative for conventional formwork in concrete construction industry due to its relatively lower cost of construction and ease of assembly. The PVC panels are joined using connectors and serve as a permanent formwork into which fresh concrete is poured to form composite PVC encased concrete walls. This study has experimentally investigated the effects of using macro-synthetic fibre reinforced concrete on the interface shear strength of composite PVC encased walls in comparison with composite PVC encased walls filled with conventional plain concrete and reinforced concrete. Nine composite PVC encased concrete wall specimens were cast and tested using direct shear tests. Based on the load–deflection curves obtained from the direct shear tests, the maximum shear loads and interface shear strength values were determined for three different cases including i) test specimens filled with plain concrete, ii) test specimens filled with macro-synthetic fibre reinforced concrete, and iii) test specimens filled with reinforced concrete. The determined parameters as well as the measured load–deflection curves for the three cases were compared and the final findings have been discussed. Based on the outcomes of this study, it has become apparent that the tested composite PVC encased macro-synthetic fibre reinforced concrete wall specimens can noticeably exhibit higher interface shear strength values compared to the tested wall specimens filled with plain concrete. Since AS 3600 (2018) does not prescribe the shear plane surface coefficients for determining the interface shear strength of composite PVC encased concrete walls, in order to enable structural designers to determine the interface shear strength for those panels using AS 3600 (2018), those coefficients have been extracted from the test results for the three mentioned cases and proposed for practical applications.